High-resolution, in vivo multimodal photoacoustic microscopy, optical coherence tomography, and fluorescence microscopy imaging of rabbit retinal neovascularization. Issue 1 (December 2018) - Zhang, Wei; Li, Yanxiu; Nguyen, Van; Huang, Ziyi; Liu, Zhipeng; Wang, Xueding; Paulus, Yannis
Abstract Photoacoustic microscopy (PAM) is an emerging imaging technology that can non-invasively visualize ocular structures in animal eyes. This report describes an integrated multimodality imaging system that combines PAM, optical coherence tomography (OCT), and fluorescence microscopy (FM) to evaluate angiogenesis in larger animal eyes. High-resolution in vivo imaging was performed in live rabbit eyes with vascular endothelial growth factor (VEGF)-induced retinal neovascularization (RNV). The results demonstrate that our multimodality imaging system can non-invasively visualize RNV in both albino and pigmented rabbits to determine retinal pathology using PAM and OCT and verify the leakage of neovascularization using FM and fluorescein dye. This work presents high-resolution visualization of angiogenesis in rabbits using a multimodality PAM, OCT, and FM system and may represent a major step toward the clinical translation of the technology. Imaging eye disease A multimodal imaging system which can visualize abnormal new blood vessels in the retina and choroid could be a useful future tool for diagnosing and monitoring eye diseases. Retinal neovascularization can lead to significant loss of vision through diseases such as age-related macular degeneration, diabetic retinopathy, sickle cell retinopathy, and retinal vein occlusions. This manuscript describes a novel high-resolution imaging system that combines optical coherence tomography (OCT), photoacoustic microscopy (PAM), and fluorescence microscopy (FM) and demonstrates that it can visualize neovascularization in the eyes of living rabbits.